The impact of the 4 h target on patient care and outcomes in the Emergency Department: an analysis of hospital incidence data. Issue 12 (13th May 2010) - Freeman, Jenny V; Croft, Susan; Cross, Sue; Yap, Chris; Mason, Suzanne
Abstract : Background: Recent government initiatives in the NHS have seen patient care becoming increasingly target-driven. However, the impact of targets, particularly those based on a timeframe, have not been extensively studied, and concerns remain about unintended consequences for patients. The aim of this study was to evaluate the effect of a 4 h target in the Emergency Department (ED) on patient care and outcomes. Methods: The study comprised an interrupted time-series regression analysis of anonymised patient-level data from 580 000 new patient episodes in the ED between April 2000 and Feb 2006. Outcomes were time in ED, time to clinician, mortality, admission and reattendance rates, and number of investigations. Results: 90% target was associated with reductions in time in department and fewer patients admitted for less than 24 and 48 h, and a slight increase in the number reattending within 7 days. 98% target was associated with levelling-off of time in department and reductions in numbers admitted and reattending within 7 days. Neither target was associated with change in time to clinician. The introduction of a minor injuries unit (MIU) was associated with reductions in time to clinician and percentage not waiting, and increases in number of investigations, percentages admitted, admitted for 24 h and reattendances within 7 days. Mortality was unaffected by either target or MIU. Conclusion: Although time target introduction is associated with changes in patient care, the introduction of a co-located MIU had greater impact.